Evaluating the quality of educational services according to the modified Servqual modelStudy of a sample of students of the Faculty of Management and Economics / University of Baghdad - الجلبي صباح عبد الحسن (Journal of Economics and Administrative Sciences, 2009)
The research aims to apply a modified SERVQUAL model to evaluate the quality of the educational services via conducting exploratory research for students from the College of Administration and Economics- Department of Business Administration- Evening studies at the University of Baghdad. Questionnaire of two parts was distributed to a sample of (72) students out of (720) students of the 2nd.,3rd. and 4th. year in the beginning of the second semester of the year 2008-2009 to measure the expectations and perceptions to the quality of the educational services. Five major dimensions were analyzed to see the gaps for (22) variables. The study concluded that there were (13) variables confirmed that the expectations were below the perceptions while (9) variables were satisfying to the students. The fifth dimension was the first in the importance and the third one was the second, whereas the first one was the least in the importance for all of them.